Cornuside ameliorated experimental autoimmune encephalomyelitis by limiting the recruitment of CD4+ T lymphocytes in the spinal cord - Rongbo Zhang; Shuijing Zhang; Bin Xu; You Wu; Shunli Liang; Bonan Hou; Mimi Wang; Jin Liu; Qiang Yuan (Universidade de São Paulo, 2022)
Abstract We conducted this study to determine whether cornuside could improve the neurological deficit symptoms of experimental autoimmune encephalomyelitis (EAE) rats, as well as determine the potential involvement of CD4+ T lymphocytes, vascular cell adhesion molecule-1 (VCAM-1), intercellular adhesion molecule-1 (ICAM-1), and tumor necrosis factor-α (TNF-α). Altogether, 32 Lewis rats were randomly divided into control, EAE, EAE/prednisolone, and EAE/cornuside, wherein their neurological function was assessed every day. CD4+ T lymphocyte recruitment into the spinal cord (SC) was evaluated using immunohistochemistry. The VCAM-1, ICAM-1 and TNF-α mRNA expressions in the SC were determined by real-time quantitative PCR, and the VCAM-1 and ICAM-1 proteins were determined by western blotting. Compared to the control group, the EAE group rats with neurological deficits had enhanced CD4+ T lymphocyte infiltration and higher expression levels of VCAM-1, ICAM-1, and TNF-α in the SC. Meanwhile, compared with the EAE group, the EAE/cornuside and EAE/prednisolone groups had lower neurological scores, less CD4+ T lymphocyte infiltrations, and lower expression levels of VCAM-1, ICAM-1, and TNF-α in the SC. Thus, cornuside ameliorated EAE, which could be owed to the inhibition of CD4+ T lymphocyte recruitment and VCAM-1, ICAM-1, and TNF-α expressions in the SC.